Propostas para melhoria da gestão da manutenção em uma indústria de produtos de higiene pessoal - Valentim, Murillo de Moraes (2020)
In the present work, the Key Performance Indicators (KPI) of maintenance were determined for a company of personal hygiene products. The study involved adapting the company's internal processes in order to obtain reliable data for calculating the indicators. Average Time to Repair (MTTR), Average Time Between Failures (MTBF), machine availability, back log and maintenance profile were evaluated. The analysis of these indicators provide a view of the characteristics of this company, guiding the Maintenance Planning and Control (PCM) team, aiming at maximum asset availability, production reliability and increasing the company's profit by reducing maintenance costs.